Three-Dimensional Computed Tomography Scanning of Temporal Vessels to Assess the Safety of Filler Injections. (27th February 2021) - Chen, Chun-Lin; Cong, Li-Yao; Kong, Xiang-Xue; Zhao, Wei-Rui; Hong, Wei-Jin; Luo, Cheng-En; Luo, Sheng-Kang
Abstract: Background: Temple filler injection is one of the most common minimally invasive cosmetic procedures involving the face; however, vascular complications are not uncommon. Objectives: This study aimed to investigate the anatomy of the temporal vessels and provide a more accurate protocol for temple filler injection. Methods: Computed tomography (CT) scans of 56 cadaveric heads injected with lead oxide were obtained. We then used Mimics software to construct 3-dimensional (3D) images of the temporal vessels described by a coordinate system based on the bilateral tragus and right lateral canthus. Results: In the XOY plane, the superficial temporal artery (STA), middle temporal artery (MTA), zygomatico-orbital artery (ZOA), posterior branch of the deep temporal artery (PDTA), and lateral margin of the orbital rim divide the temple into 4 parts (A, B, C, and D). The probabilities of the STA, MTA, ZOA, and PDTA appearing in parts A, B, C, and D were 30.73%, 37.06%, 39.48%, and 77.18%, respectively. In 3D images, these vessels together compose an arterial network that is anastomosed with other vessels, such as the external carotid, facial, and ocular arteries. Conclusions: 3D CT images can digitally elucidate the exact positions of temporal vessels in a coordinate system, improving the safety of temple filler injections in a clinical setting.